THE COMMUNITY STRATEGY OF THE YOUTH MOVEMENT TO LOVE MOSQUES IN PROSPERING THE MOSQUE IN SAMPALI VILLAGE - Kurnia Ramadhan; Faridah Faridah (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2026)
This study examines the community-based strategy developed by the Youth Movement for Mosque Love, known locally as Gerakan Pemuda Cinta Masjid (GPCM), in revitalizing the prosperity of mosques in Sampali Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra. Using a qualitative descriptive approach, data were collected through in-depth interviews, direct observation, and documentation involving GPCM administrators, mosque officials, and congregation members as key informants (Abdussamad, 2021; Sugiyono, 2016). The findings show that GPCM strengthens mosque functions through four interrelated efforts: sustaining routine religious study circles, engaging youth directly in mosque programs, organizing religious and social welfare activities, and utilizing social media for da'wah dissemination (Nudin & Fakhruroji, 2023). Despite constraints such as limited funding and coordination gaps, the community's enthusiasm and its collaborative relationship with mosque administrators have revived congregational participation and social cohesion, positioning the mosque once again as the center of communal religious life.